Improved serum stability and biophysical properties of siRNAs following chemical modifications - Cho, Ik Sang; Kim, Jung; Lim, Do Hwan; Ahn, Hee-Chul; Kim, Hyunggee; Lee, Kang-Bong; Lee, Young Sik (SPRINGER, 2008)
Small interfering RNAs (siRNAs) which mediate sequence-specific gene silencing through RNA interference have been harnessed for therapeutic applications. Here, we found combinations of modest 2'-ribose siRNA modifications that permit effective gene silencing and improve siRNA stability in human serum. Introduction of as few as two different or identical 2'-ribose modifications at a specific position of either strand, which has been previously suggested to suppress unintended off-target effects, enhances the thermal and thermodynamic stability of siRNA duplexes, and does not alter the overall A-form helical geometry that is required for silencing activity. Our results provide a useful template for the design for therapeutic siRNAs.
Keywords: SMALL INTERFERING RNA; FUNCTIONAL FEATURES; STRUCTURAL BASIS; DEGRADATION; RECOGNITION